Marketing the availability of secondary and specialized medical care services in the health care system (Economics and region, 2022)
The article carries out a marketing analysis of the levels of availability for patients of secondary and specialized health care services provided by secondary and tertiary health care institutions. A theoretical analysis of research by foreign scientists on the problem of levels of accessibility of various categories of patients to medical care was carried out. It was found that patients with concomitant chronic diseases have certain barriers to access to secondary and specialized medical care. The dynamics of the respondents' assessment of changes in the main types of availability of medical services for the population (quality of medical care and financial availability), which are provided by specialized doctors in polyclinics and hospitals, are characterized. The main indicators of changes in the levels of availability of medical services, which were provided by narrow-profile doctors in the polyclinic and in the hospital (inpatient), were analyzed. The main types of availability of medical services, which according to the respondents have an important influence on the level of medical care, were studied. The main three types of availability of medical services are distinguished: the quality of the provision of medical services, financial availability and territorial or temporal availability of medical services. The main constituent factors of the availability of medical services are characterized, in particular, the quality of the provision of medical services (treatment of patients by doctors and medical personnel; professionalism of doctors; efficiency (effectiveness) of treatment; conditions in which medical care is provided (repair, cleanliness of premises, including bathrooms), financial availability (possibility to purchase or obtain medication according to the doctor’s prescription, ability to receive treatment, including consultation, diagnostic and laboratory examinations, medical procedures, availability of equipment in the institution and the possibility to receive medical services using it), territorial or temporal availability of medical services (the possibility of choosing a doctor, the duration of waiting for a doctor, the schedule of a doctor’s appointment, the possibility of making an appointment in advance for an appointment with a doctor at the right time, the territorial convenience of the location of a medical institution and communication with it). and the tertiary link of medical services, will become a kind of indicator of availability for patients in case of need to receive timely and effective treatment and will contribute to their satisfaction with medical services.
Keywords: medical service; quality of provided medical services; financial availability; territorial or temporal availability of medical services; specialized specialists in the polyclinic; secondary and tertiary (highly specialized) link of medical services